Prinsip Isonomi di Indonesia: Filosofi, Makna, dan Perbandingan - Titon Slamet Kurnia (Jurnal Konstitusi, 2022)
The regulation of the principle of isonomy in Article 28D paragraph (1) of the 1945 Constitution of the Republic of Indonesia and its derivative laws without an explanation of its meaning has implications for misunderstanding what it means. This study seeks answers to the philosophical question and the meaning of the isonomy principle and compares it with the isonomy principle in English law which is based on the rule of law. Using theoretical research, three answers were obtained. The social contract which contains an agreement on the surrender of natural rights to enforce law by individuals to the state and places individuals in the same position and treatment in law enforcement by the state becomes a philosophy of isonomy principles. The principle of isonomy in Indonesia is based on distributive justice where equal treatment before the law means proportionality with regard to people's class, position, achievements, and functions of people in the social order. In English law, the principle of isonomy is based on commutative justice where all people regardless of class, position, social status or function, they are under the same law and justice.